Pengaruh Pendidikan HIV dan AIDS Menggunakan Metode Diskusi Kelompok Kecil dengan Fasilitator Terhadap Tingkat Pengetahuan dan Sikap Ibu Rumah Tangga di Rusun Begalon Surakarta - Kurniawati, Fifit; , Yuli Kusumawati, SKM., M. Kes (Epid); , Farid Setyo Nugroho, SKM (2015)
The data based on the National AIDS Commission in 2014 showed the distribution of AIDS cases by type of work, IRT with HIV and AIDS in recent years increased to 18.4% and was ranked second. The purpose of this study was to analyze the effect of HIV and AIDS education using small group discussions with facilitators on the level of knowledge and attitudes IRTinFlat Begalon Surakarta. This research uses quasi experimental with pretest-posttest design with control group. The population in this study is the IRT as many as 192 people. Selection ofsamples usingSimpleRandom Sampling, divided intotwogroups:the experimental groupand the groupcontrolwith72samples.Statistical testusingPairedsample t-test, showednodifference inthe average scoreof knowledge(p =0.000) and attitude(p =0.000) in the experimental groupaftertreatmentandnodifference inmean scoreof knowledge(p =0.000) andattitude(p =0.000) in the control group.The test results Independent sample t-test showed no effect of health education on HIV and AIDS using small group discussions with facilitators to knowledge (p = 0.000) and attitude (p = 0.000) IRT about HIV and AIDS. Keywords: Health education. HIVandAIDS. method ofsmall group discussions withfacilitators